The Relationship between Language Attitude and Communicative Performance in Arabic Language Learning - Fatwa Arifah; Puti Zulharby; Haniah Haniah; Abeer Salaheldin Heider (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2026)
Background: Arabic language learning in Indonesian higher education occupies a distinctive position because it is linked not only to academic development but also to religious and cultural identity. Despite generally positive attitudes toward Arabic, many students continue to struggle with utilizing the language effectively in authentic communication. Research Objectives: This study aims to examine and explain the relationship between students’ language attitudes and their communicative performance in Arabic learning. Methodology: This study employed an explanatory sequential mixed-methods design. The quantitative phase involved 166 students from the Arabic Language Education programs at Universitas Negeri Jakarta and UIN Alauddin Makassar, selected through purposive sampling. Data were collected using a 30-item Likert-scale questionnaire and analysed through descriptive statistics, Pearson correlation, and ANOVA. The qualitative phase involved semi-structured interviews with selected participants; these data were thematically analyzed to explain the quantitative findings. Results: The results revealed a strong and statistically significant positive correlation between language attitude and communicative performance (r = 0.650, p < 0.01). Although 57.8% of students demonstrated highly positive attitudes toward Arabic, only 17.5% achieved high communicative performance. The qualitative findings further indicated that communicative performance was influenced by educational background, institutional environment, confidence, and opportunities for authentic interaction. Unique Contribution: This study contributes empirical evidence to the literature on language attitude and communicative behaviour by examining Arabic language learning in the underexplored context of Indonesian higher education through a mixed-methods approach. Conclusion: While positive language attitudes provide a crucial foundation for Arabic proficiency, their pedagogical impact is contingent upon the availability of communicative, interactive, and contextually meaningful learning environments. Recommendations: Further studies are recommended to examine additional contextual and affective variables, such as anxiety, classroom interaction, and willingness to communicate, that may mediate the relationship between language attitude and communicative performance.